Bone marrow sinusoidal endothelium controls terminal erythroid differentiation and reticulocyte maturation - Joschka Heil (Nature Portfolio, 2021)
Niche crosstalk with Haematopoietic cells underlies normal haematopoiesis and myeloid disorders. Here the authors report a Stabilin2-Cre driver mouse with Cre-activity restricted to bone marrow sinusoidal endothelial cells, and that Stabilin2-Cre driven overactivation of b-catenin leads to erythroid differentiation defects and anaemia.